Status of local participation in forest resources management in Southwest Nigeria (2007)
Community-based forest management has evolved in the past decade as an approach for the sustainable management of forest resources. This study investigated the status of local participation in forest resources management in Southwestern Nigeria. Study sites were selected using a combination of purposive and random sampling techniques from the six states within the region. The target population for the study were ‘the Public’, timber contractors and sawmillers (TCS) as well as forestry officials. Data, which were collected using structured questionnaires and Focus Group Discussions (FGDs) were analyzed using descriptive and Chi Square statistics. Results revealed that Community-based forest management (CBFM) was not in practice in Southwestern Nigeria. Awareness of this initiative varied significantly among the three stakeholders interviewed for the study (the public = 23.8%; TCS = 56.5%; Forestry officials = 84.5%). Identified factors responsible for the non-existence of CBFM included non introduction of the management strategy by the government; lack of awareness on the part of the public; lack of policies and legislations to back up the management strategy; lack of institutional strategy/framework for CBFM at State Department of Forestry level among others. Meanwhile, there is a strong relationship between management styles of forest reserves and the inability of government to alone solve the problem of forest degradation (Pr < 0.01, χ2 = 11.146, df = 3). The pronouncement of new policies and promulgation of new laws in respect of participatory initiative will be the basis for sound footing of CBFM in the study area. A valuable starting point will be the raising of awareness level on this initiative, and also improving and strengthening relationships among stakeholders.